(untitled) (Gestão & Regionalidade, 2021)
The article aims to analyze the innovative behavior under the dimensions presented in De Jong and Den Hartog’s (2010) study from the manager and employee perspective in Minas Gerais’ industrial sector. The study of the employee’s perception was used to research the studies carried out by Scott and Ruce (1994) and Janssen (2000). It is descriptive research with a quantitative methodology, carried out through SurveyMonkey between November 2016 and May 2017. It was noticed a significant motivation of the managers to prompt the innovative behavior in the employees. However, little was perceived from the employees’ perspective, corroborating with the academy results in which the managers and employees need to converge for the organizational development. In this way, the company will have opportunities to excel in the industry. Keywords: innovation; innovative behavior; automotive industry